Manajemen Stratak Pendidikan Karakter Dalam Meningkatkan Perilaku Positif Siswa: Penelitian - Renyta Susiari; Ahmad Thohirin; Suyitno; A. Faizin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aimed to describe the management of strategies and tactics (stratak) of character education in improving students’ positive behavior at SDN Karangjati III, Pandaan District, Pasuruan Regency. A qualitative approach with a case study design was employed. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and students. Data analysis used Miles and Huberman’s interactive model. The findings indicate that character education stratak management was implemented through integrated planning, strengthening school culture, and operational tactics such as teacher role modeling, daily habituation, and the integration of character values into learning activities. These efforts contributed to improvements in students’ positive behavior, particularly discipline, responsibility, respect, and cooperation.